Найти производную y=e^3x * (sinx - cosx)

+1
Ответы (1)
  1. 20 июня, 07:53
    0
    Производная равна:

    y ' = (e^ (3 * x) * (sin x - cos x)) ' = (e^ (3 * x)) ' * (sin x - cos x) + (sin x - cos x) ' * e^ (3 * x) = e^ (3 * x) * (3 * x) ' * (sin x - cos x) + (sin ' x - cos ' x) * e^ (3 * x) = 3 * e^ (3 * x) * (sin x - cos x) + e^ (3 * x) * (cos x - (-sin x)) = 3 * e^ (3 * x) * (sin x - cos x) + e^ (3 * x) * (cos x + sin x)) = 3 * e^ (3 * x) * sin x - 3 * e^ (3 * x) * cos x + e^ (3 * x) * cos x + e^ (3 * x) * sin x = 4 * e^ (3 * x) * sin x - 2 * e^ (3 * x) * cos x;

    Ответ: y ' = 4 * e^ (3 * x) * sin x - 2 * e^ (3 * x) * cos x.
Знаешь ответ на этот вопрос?